Preliminary data on attractiveness of phenylacetaldehyde-based lures on economically important plant bug pests (Hemiptera: Miridae) - Szalárdi, T.; Nagy, A.; Oláh, F.; Tóth, M.; Koczor, S. (International Journal of Horticultural Science, 2021)
Several plant bug species (Miridae) are important pests of crops and vegetables, thus monitoring them is of essential importance for effective pest control. During the current, preliminary study synthetic plant volatile combinations were tested in field conditions in Hungary in alfalfa fields. Beside semiochemical baited traps, sweep-netting was also performed. In the experiments three plant bug species were found in higher numbers: Adelphocoris lineolatus, Lygus rugulipennis and L. pratensis. As a novel, interesting finding L. pratensis was attracted to phenylacetaldehyde baited traps. For all species, both males and females were trapped in all combinations. Sweep-netting and semiochemical baited traps showed different efficacy in case of the three species, as sweep-netting catches were highly biased for A. lineolatus, which indicates the higher efficacy of this method as compared to the tested semiochemical-baited traps. On the other hand, semiochemical baited showed better performance for L. rugulipennis and L. pratensis. For these species none of the tested combinations performed better than phenylacetaldehyde baited traps. The potential implication of results in view of monitoring are discussed.